The Complex Thiol-Palladium Interface: A Theoretical and Experimental Study - Carro, P. (2010)
This paper presents a theoretical study of the surface structures and thermodynamic stability of different thiol and sulfide structures present on the palladium surface as a function of the chemical potential of the thiol species. It has been found that as the chemical potential of the thiol is increased, the initially clean palladium surface is covered by a ( √ 3 x √ 3)R30º sulfur lattice. Further increase in the thiol pressure or concentration leads to the formation of a denser ( √ 7 x √ 7)R19.1º sulfur lattice, which finally undergoes a phase transition to form a complex ( √ 7 x √ 7)R19.1º sulfurþ thiol adlayer (3/7 sulfur þ 2/7 thiol coverage). This transition is accompanied by a strong reconstruction of the Pd(111) surface. The formation of these surface structures has been explained in terms of the catalytic properties of the palladium surface. These results have been compared with X-ray photoelectron spectroscopy results obtained for thiols adsorbed on different palladium surfaces.